2002
DOI: 10.1007/s003800200028
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerotic burden in coronary and peripheral arteries in patients with first clinical manifestation of coronary artery disease

Abstract: The aim of our study was to assess the atherosclerotic burden in patients with the first symptoms of coronary artery disease (CAD). The study population consisted of 100 consecutive patients (new-onset severe angina or myocardial infarction) and 70 age- and sex-matched volunteers without symptoms of CAD. Functional and morphologic atherosclerotic markers were sought in carotid, brachial, and femoral arteries of all subjects by means of high-resolution ultrasonography while coronary arteriography was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 38 publications
1
17
0
1
Order By: Relevance
“…Previous studies show that FMD and IMT are both significant predictors for significant coronary artery disease [11,[27][28][29]. However, some reports suggested that FMD is better than IMT for predicting coronary artery disease, [30,31] while others show the opposite finding [11,32,33].…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies show that FMD and IMT are both significant predictors for significant coronary artery disease [11,[27][28][29]. However, some reports suggested that FMD is better than IMT for predicting coronary artery disease, [30,31] while others show the opposite finding [11,32,33].…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, the presence of CS and PAD suggests more advanced CAD and patients with CAD are younger than patients with CS and/or PAD. [25][26][27][28][29] Taking those findings into consideration, coronary atherosclerosis may tend to progress in the early stage of generalized atherosclerosis. Moreover, as the present study shows, the presence of one atherosclerotic disease is a clue to the presence of another in a cohort of CAD patients.…”
Section: Discussionmentioning
confidence: 99%
“…4 It is estimated that the first manifestation of coronary artery disease (CAD) in 60-70% of patients is either sudden death or myocardial infarction, whereas only a minority present first with angina or other symptoms of reversible ischemia. 5 The reason for the onset of symptoms late in the disease process is not known but could be related to an impairment in, or inadequate fidelity of the cardiac sensory mechanism responsible for signaling myocardial ischemia.…”
mentioning
confidence: 99%